Pengembangan Media Pembelajaran Interaktif Berbasis Google Sites pada Mata Pelajaran Informatika Materi Jaringan Komputer dan Internet di Kelas XI Peminatan Informatika di SMA 11 Samarinda - Aji Muhammad Riziq Al Farid; Ramaulvi Muhammad Akhyar (Jurnal Pendidikan Indonesia, 2026)
This study aims to develop interactive learning media based on Google Sites for the Informatics subject, specifically the Computer Networks and Internet topic, for Grade XI specialization students at SMA Negeri 11 Samarinda. The development of this learning media was motivated by the rapid advancement of information technology, which requires the education sector to adopt more innovative and interactive learning methods. Based on observations, conventional learning media such as PowerPoint presentations, printed modules, instructional videos, and WhatsApp groups tend to be monotonous and less effective in enhancing students’ learning motivation. This study employed the Planning, Production, and Evaluation (PPE) development model. Data were collected through observation, interviews, and questionnaires, while data analysis was conducted using descriptive quantitative analysis. The research involved two media experts, one subject-matter expert, and 37 Grade XI specialization students as product trial participants. The validation results showed that the developed learning media achieved an average score of 4.6 from media experts and 4.3 from the subject-matter expert, both categorized as highly feasible, while students’ responses reached 82.57%, indicating a positive evaluation. The learning media includes learning materials, educational content, and interactive quizzes that can be accessed through any internet-connected device. The Google Sites-based platform effectively enhances student engagement, provides flexible access to learning resources, and serves as an effective digital learning solution to support students’ readiness for technological advancements and future careers in the digital workforce.